2007
DOI: 10.1111/j.1365-2966.2007.12255.x
|View full text |Cite
|
Sign up to set email alerts
|

The history of star-forming galaxies in the Sloan Digital Sky Survey

Abstract: We study the evolution of 82302 star-forming (SF) galaxies from the SDSS. Our main goals are to explore new ways of handling star formation histories (SFH) obtained with our publicly available spectral synthesis code STARLIGHT, and apply them to investigate how SFHs vary as a function of nebular metallicity (Zneb). Our main results are: (1) A conventional correlation analysis shows how global properties such as luminosity, mass, dust content, mean stellar metallicity and mean stellar age relate to Zneb. (2) We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
322
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(342 citation statements)
references
References 72 publications
(129 reference statements)
18
322
0
2
Order By: Relevance
“…We attempted to reproduce the spectral absorption lines and continua of the sample galaxy spectra to study their stellar populations by using the software STARLIGHT 5 (Cid Fernandes et al 2005, 2007Mateus et al 2006;Asari et al 2007;Chen et al 2009). This is a program that fits an observed spectrum O λ with a model M λ that combines up to N * SSPs with different ages and metallicities from different stellar population synthesis models.…”
Section: Spectral Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted to reproduce the spectral absorption lines and continua of the sample galaxy spectra to study their stellar populations by using the software STARLIGHT 5 (Cid Fernandes et al 2005, 2007Mateus et al 2006;Asari et al 2007;Chen et al 2009). This is a program that fits an observed spectrum O λ with a model M λ that combines up to N * SSPs with different ages and metallicities from different stellar population synthesis models.…”
Section: Spectral Synthesis Methodsmentioning
confidence: 99%
“…Cid Fernandes and his colleagues have studied the spectral synthesis on the SDSS galaxies by using the BC03 model and their STARLIGHT code. They also measured the properties of the galaxies, such as the dust extinction, stellar mass, SFH (Cid Fernandes et al 2004, 2007Mateus et al 2006;Asari et al 2007Asari et al , 2009Stasińska et al 2008). Koleva et al (2008) compared different models, and found that the Pégase-HR (Le Borgne et al 2004) and Vazdekis/Miles models were in precise agreement, while the BC03 model exhibited biases, which might be due to the poor metallicity coverage of STELIB library causing unreliable results at non-solar metallicities.…”
Section: Introductionmentioning
confidence: 99%
“…We used the SDSS-DR5 spectra from the STARLIGHT database 1 , which were processed through the STARLIGHT spectral synthesis code, developed by Cid Fernandes and colleagues (Cid Fernandes et al 2005Mateus et al 2006;Asari et al 2007). From them, we obtained the emission lines fluxes measurements of our samples from the contiuum subtracted spectra.…”
Section: Sample Selectionmentioning
confidence: 99%
“…To this aim, our sample is divided in redshift intervals of 0.1 from z ∼ 0 to 0.4. The purpose for selecting small ranges in luminosity is to alleviate the problem of the magnitude completeness, since the Sloan sample is only complete in the magnitude range 14.5 < m r < 17.7 (e.g., Asari et al 2007), and then becomes incomplete at redshift above z > 0.1 (e.g., Kewley et al 2006). However, this procedure limits the study to the more luminous galaxies, since they are the ones detected at any redshift interval.…”
Section: Sample Selectionmentioning
confidence: 99%
“…The AGB phase of intermediate mass stars (1 M⊙ 8) and massive stars ( 8M⊙) which end their lives as Type II supernovae (SNe) are considered the dominant source of stellar dust production in star-forming galaxies while dust in the ISM may also form in situ from accretion of enriched gas processed by stars (Dwek 1998). Dust forms from metals and a strong correlation between gas-phase oxygen abundance and dust content is observed in local (Heckman et al 1998;Boissier et al 2004;Asari et al 2007;Garn & Best 2010;Xiao et al 2012;Zahid et al 2012b) and high redshifts galaxies Domínguez et al 2013).…”
Section: Introductionmentioning
confidence: 99%